2007
DOI: 10.1093/toxsci/kfm217
|View full text |Cite
|
Sign up to set email alerts
|

Adsorbed Proteins Influence the Biological Activity and Molecular Targeting of Nanomaterials

Abstract: The possible combination of specific physicochemical properties operating at unique sites of action within cells and tissues has led to considerable uncertainty surrounding nanomaterial toxic potential. We have investigated the importance of proteins adsorbed onto the surface of two distinct classes of nanomaterials (single-walled carbon nanotubes [SWCNTs]; 10-nm amorphous silica) in guiding nanomaterial uptake or toxicity in the RAW 264.7 macrophage-like model. Albumin was identified as the major fetal bovine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
297
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 415 publications
(309 citation statements)
references
References 33 publications
12
297
0
Order By: Relevance
“…These data indicated that MNPs internalization might affect also the ratio between the serum proteins and the amount of nanoparticles. The protein corona has been shown to be a dynamic structure, largely determined by the extracellular milieu [35,36], and substantially influences dispersion, biodistribution, mechanism of internalization and biological activity of nanoparticles [33,37]. Albumin, fibrinogen and immunoglobulins (Ig) have been shown to be the principal plasma proteins that bind to iron oxide nanoparticles when they come in contact with plasma [38].…”
Section: Discussionmentioning
confidence: 99%
“…These data indicated that MNPs internalization might affect also the ratio between the serum proteins and the amount of nanoparticles. The protein corona has been shown to be a dynamic structure, largely determined by the extracellular milieu [35,36], and substantially influences dispersion, biodistribution, mechanism of internalization and biological activity of nanoparticles [33,37]. Albumin, fibrinogen and immunoglobulins (Ig) have been shown to be the principal plasma proteins that bind to iron oxide nanoparticles when they come in contact with plasma [38].…”
Section: Discussionmentioning
confidence: 99%
“…In one study, it was also found to be the most abundant protein in the hard corona of silica NPs, 59 while in other cases, its content in the hard protein corona was very low. [60][61][62] Physical parameters such as the surface curvature of NPs were proposed to play a role in the competitive adsorption of proteins in the process, resulting in the formation of the hard corona. 22 It could be of interest to investigate the possible contribution of different amounts and distributions of surface silanols to the composition of the hard protein corona on SiO 2 NPs.…”
Section: Cd-uv Spectra Of Irreversibly Adsorbed Proteinsmentioning
confidence: 99%
“…As reported previously, the protein corona on nanoparticles would critically impact the biological identities of nanoparticles [6][7][8][9] and/or result in the physiological and pathological consequences of the macrophage uptake, blood coagulation, complement activation and cellular toxicity, etc. [10][11][12][13][14][15][16]. The elaborate investigation on protein corona would accordingly make great sense for the extensive application of nanomaterials.…”
Section: Introductionmentioning
confidence: 99%